Sinistrals are rarely “right”: evidence from tool-affordance processing in visual half-field paradigms - Michałowski, Bartosz; Króliczak, Gregory (Frontiers in Human Neuroscience, 2015)
Although current neuroscience and behavioral studies provide substantial understanding of tool representations (e.g., the processing of tool-related affordances) in the human brain, most of this knowledge is limited to right-handed individuals with typical organization of cognitive and manual skills. Therefore, any insights from these lines of research may be of little value in rehabilitation of patients with atypical laterality of praxis and/or hand dominance. To fill this gap, we tested perceptual processing of man-made objects in 18 healthy left-handers who were likely to show greater incidence of right-sided or bilateral (atypical) lateralization of functions. In the two experiments reported here, participants performed a tool vs. non-tool categorization task. In Exp. 1, target and distracter objects were presented for 200 ms in the left (LVF) or right (RVF) visual field, followed by 200ms masks. In Exp. 2, the centrally presented targets were preceded by masked primes of 35ms duration, again presented in the LVF or RVF. Based on results from both studies, i.e., response times to correctly discriminated stimuli irrespective of their category, participants were divided into two groups showing privileged processing in either left (N = 9) or right (N = 9) visual field. In Exp. 1, only individuals with RVF advantage showed significantly faster categorization of tools in their dominant visual field, whereas those with LVF advantage revealed merely a trend towards such an effect. In Exp. 2, when targets were preceded by identical primes, the ‘atypical’ group showed significantly facilitated categorization of non-tools, whereas the ‘typical’ group demonstrated a trend towards faster categorization of tools. These results indicate that in subjects with atypically organized cognitive skills, tool-related processes are not just mirror reversed. Thus, our outcomes call for particular caution in neurorehabilitation directed at left-handed individuals.